2022
DOI: 10.48550/arxiv.2201.09306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quintessence or Phantom: Study of scalar field dark energy models through a general parametrization of the Hubble parameter

Abstract: In this work we propose a simple general parametrization scheme of the Hubble parameter for the scalar field dark energy models. In our approach it is possible to incorporate both the quintessence and phantom scalar field in a single analytical scheme and write down relevant cosmological parameters which are independent of the nature of the scalar field. A general condition for the phantom barrier crossing has also been obtained. To test this approach, a well behaved parametrization of the normalized Hubble pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Dropping the field interpretation of DE, it is possible to explore models in which DE sector deviates from the cosmological constant to a DE fluid with an extended EoS parameter w DE = −1, which can generally vary with redshift. These dynamical dark energy (DDE) models have been extensively studied in the literature [24,183,252,457,641,[728][729][730][731][732][733][734][735], based on considerations over the reconstruction of the effective w DE from data [183]. 16 DDE models typically solve the H 0 tension within two standard deviations at the price of a phantom-like DE, i.e.…”
Section: Dynamical Dark Energymentioning
confidence: 99%
“…Dropping the field interpretation of DE, it is possible to explore models in which DE sector deviates from the cosmological constant to a DE fluid with an extended EoS parameter w DE = −1, which can generally vary with redshift. These dynamical dark energy (DDE) models have been extensively studied in the literature [24,183,252,457,641,[728][729][730][731][732][733][734][735], based on considerations over the reconstruction of the effective w DE from data [183]. 16 DDE models typically solve the H 0 tension within two standard deviations at the price of a phantom-like DE, i.e.…”
Section: Dynamical Dark Energymentioning
confidence: 99%
“…According to Agostino et al [33], if the thermodynamics for a generalized scalar (dark) matter field is expressed in terms of a quasi-quintessence representation, the vacuum energy contribution can be removed. For the scalar field dark energy models, Roy et al [34] suggested a simple generalized parameterization approach of the Hubble parameter. With their method, it is possible to write down relevant cosmological parameters that are independent of the scalar field's nature while incorporating both the quintessence and phantom scalar fields into a single analytical scheme.…”
Section: Introductionmentioning
confidence: 99%